Conceptualising Inclusive Education: Insights from South African Primary School Principals - Zakhele Dennis Nzuza; Jamiu Temitope Sulaimon (Universitas Muhammadiyah Surakarta, 2025)
This study explores the understanding of inclusive education by principals in South African primary schools. It draws on in-depth research and reflective engagements over the past 30 years on the implementation of inclusive education in South African schools. Although the South African government introduced and adopted various policies, understanding the concept of inclusive education in the education sector remains contentious. This research focusses on understanding the principles and practices of inclusive education in schools, ensuring that all students have equal access to learning opportunities. Research objectives have been sharpened to investigate the implementation of inclusive education, accommodating different types of learners, and strategies used to promote a supportive learning environment. A qualitative case study design was used in the six primary schools in the uMgungundlovu district, South Africa, to encourage a deeper understanding of inclusive education as a concept within general education. The data collected were analyzed using content analysis. By examining various aspects of inclusive education, this study uncovers the essential role of educators in fostering an inclusive classroom culture that satisfies the diverse needs of all learners. The study concludes that inclusive education involves holistically teaching all learners by implementing differentiated instruction with adequate support for diverse learners. The findings of the study have practical implications for the education sector, as they highlight the need for intensive training in higher education institutions to bridge the gap in understanding and practice of inclusive education, underlining its urgency and importance.